FAS/FASL are dysregulated in chordoma and their loss-of-function impairs zebrafish notochord formation - Ferrari, Luca (Impact Journals LLC, 2014)
Chordoma is a rare malignant tumor that recapitulates the notochord phenotype and is thought to derive from notochord remnants not correctly regressed during development. Apoptosis is necessary for the proper notochord development in vertebrates, and the apoptotic pathway mediated by Fas and Fasl has been demonstrated to be involved in notochord cells regression. This study was conducted to investigate the expression of FAS/FASL pathway in a cohort of skull base chordomas and to analyze the role of fas/fasl homologs in zebrafish notochord formation. FAS/FASL expression was found to be dysregulated in chordoma leading to inactivation of the downstream Caspases in the samples analyzed. Both fas and fasl were specifically expressed in zebrafish notochord sorted cells. fas and fasl loss-of-function mainly resulted in larvae with notochord multi-cell-layer jumps organization, larger vacuolated notochord cells, defects in the peri-notochordal sheath structure and in vertebral mineralization. Interestingly, we observed the persistent expression of ntla and col2a1a, the zebrafish homologs of the human T gene and COL2A1 respectively, which are specifically up-regulated in chordoma. These results demonstrate for the first time the dysregulation of FAS/FASL in chordoma and their role in notochord formation in the zebrafish model, suggesting their possible implication in chordoma onset.